533 Qualitative study on mass casualty responder in real field incident of Bangladesh. (20th November 2022) - Islam, Mohammad
Abstract : Background: Pre-hospital emergency medicine is undermentioned in disaster management academia and practice. In low-income countries where specialized health care is not easily available before reaching hospital for seriously ill and injured patients, local level health service provider and community people experience needs to be documented for future responds in natural disaster and man-made disaster situation. The qualitative investigation articulated the first responding experience in real field situation which has both external and internal validity for low-resource setting. Aims: The paper aims to describe experience of emergency response on mass casualty management by the service provider in real field situation. Methodology: Qualitative study conducted Focus Group Discussion with health service providers who responded for mass casualty management. Results: In qualitative investigation, most of the participants stressed on pre-hospital management and empowering local actors with necessary emergency training which will enable them to tackle post-disaster mass casualty management. It explored that we badly need of volunteers for on-site triage and lessen the mass casualty and fatality for saving maximum life with maximum effort. In post-earthquake situation, there would be lot of disaster victims; so, we need to develop the establishment of a protocol and regular mass casualty drills to cope with future occurrences. Conclusion: First responder volunteer needs to be capacitated with emergency management of injuries and resuscitation expertise for life saving solution Learning Outcomes: In Prehospital Medicine it is intellectually challenging and physically demanding work. It is also among the most fulfilling and rewarding ways to practice medicine.